Book Review - Memories of Terror: Essays on Recent History - Elizabeth Gabriele (Slovo, 2022)
Memories of Terror: Essays on Recent History is an interesting collection of essays that engages marginalized World War II stories.
Keywords: Memory; Trauma; World War II; Jewish Studies; Eastern European Studies; Transnistria; Romanian Studies; Holocaust; Lieux de Memoire; Displacement